Regular Board Meeting Agenda - Los Angeles Regional Water Quality Control Board (Los Angeles Regional Water Quality Control Board)
A variety of topics are covered regarding local environment concerns brought up by different board members that belong to different organizations. For example, Board Member Pak spoke on the issue of Halaco not being able to place permanent boundary markers until the City filed a record of survey. He asked if Halaco would respond in a timely manner to the City's requests for changes from Halaco, once the City had filed the record of survey. Etc.